Creation of Targeted Liposomes for the Delivery of Allium cepa Quercetin for Cancer Treatment - Kausar, Meena; Madhavi, Meesa; K. P, Mahesh; S. Sunitha, S. Sunitha; Pravallika, V. Santhoshi; Mugade, Megha; Waghmare, Rahul Sugriv; Averineni, Anuradha; Mukhopadhay, Keya De (Journal of Neonatal Surgery, 2025)
Introduction: Major therapeutic problems include chemotherapy-associated toxicity and multidrug resistance; cancer is still the top cause of death worldwide. Quercetin is a flavonoid that comes from the onion plant Allium cepa and has strong anticancer effects. However, it isn't very useful in the clinic because it's poorly soluble in water and has low bioavailability. The current research set out to improve quercetin's transport and therapeutic efficacy against cancer cells by creating and testing targeted liposomal formulations of the compound. Materials and Methods: An HPLC analysis was performed to determine the concentration of quercetin in the Allium cepa extract, which yielded 0.82% w/w. A 3:1 molar ratio of phosphatidylcholine to cholesterol was used to create liposomes by the thin-film hydration process. The liposome surface was modified to actively target folic acid. Drug release in vitro, entrapment efficiency, zeta potential, and particle size were all measured for the formulations. The MTT assay was used to assess cytotoxicity in MCF-7 and HeLa cancer cell lines, while confocal imaging was employed for cellular uptake studies. Results: Entrapment efficiency was 87.2 ± 2.4%, zeta potential was -28.6 ± 1.5 mV, and the average particle size of the optimized folate-targeted liposomes was 132.4 ± 3.7 nm. The sustained profile of quercetin release over 24 hours was seen in in vitro release, with a rate of 78.5 ± 2.8%. In comparison to non-targeted liposomes (IC₅₀ = 15.3 µg/mL) and free quercetin (IC₎₀ = 22.6 µg/mL), targeted liposomes showed a noticeably higher level of cytotoxicity in MCF-7 cells (IC₎₀ = 7.8 µg/mL). Research on cellular uptake has shown that liposomes coated with folate are more effectively absorbed by the body. Conclusion: Improved drug administration, cellular absorption, and anticancer activity were seen when quercetin from Allium cepa was encapsulated in foliate-targeted liposomes. To increase the bioavailability of quercetin and its therapeutic potential in cancer treatment, this tailored delivery method is an encouraging approach.